13.1k views
4 votes
If h(x) = x – 7 and g(x) = x2, which expression is equivalent to ?

(5 – 7)2
(5)2 – 7
(5)2(5 – 7)
(5 – 7)x2

1 Answer

0 votes

Answer:

Option A.

Explanation:

The given question is incomplete. Let as consider we need to find
(g\circ h)(5)

The given functions are


h(x)=x-7


g(x)=x^2

We need to find the expression for
(g\circ h)(5).


(g\circ h)(5)=g(h(5))


(g\circ h)(5)=g(5-7)
[\because h(x)=x-7]


(g\circ h)(5)=(5-7)^2
[\because g(x)=x^2]

Therefore, the correct option is A.

User Hitesh Israni
by
5.5k points